A study on the flexural behavior of sustainable concrete beams with high volume fly ash. (2020) - Joanna, P.S.; Parvati, T.S.; Rooby, Jessy; Preetha, R.
Abstract: Production of cement, the prime ingredient in concrete leads to the emission of large amount of carbon dioxide. Fly ash, a waste product from thermal power plant is emerging as an inexpensive replacement of ordinary Portland cement (OPC). The use of high volume fly ash concrete in beams requires a study on its flexural performance. Hence, this paper presents the flexural behavior of Reinforced Concrete (RC) beams with 50% fly ash as replacement to cement. Four beam specimens with High Volume Fly Ash Concrete (HVFAC) and four specimens with Ordinary Portland Cement Concrete (OPCC) were subjected to two point bending load. Data presented include the deflection characteristics, cracking behavior, ductility indices, moment curvature and end rotations of the beam specimens with sustainable concrete. The study found that the moment capacity of the HVFA beams was slightly more than that of the OPCC specimens at the end of 56 days and also the deflections under design service loads were within the allowable limits. The HVFA specimens also exhibited lesser embodied energy and embodied carbon as compared to OPCC specimens.